Assessing the Marketability of BEU as a Loungewear Brand Producing Ethically-Made and Gender-Inclusive Clothing in the Philippines - Alonte, Carlos Miguel G. (Animo Repository, 2021)
BEU is an ethical and gender-inclusive brand that aims to provide its customers with high-quality loungewear products promoting a more sustainable approach in terms of manufacturing and purchasing contemporary clothing pieces while striving for inclusivity through their brand’s motto “Be You” encouraging individuals to be who they are in the clothes they wear. BEU’s products within the market are manufactured by an ethical business: Candid Clothing. The material utilized for the production is French Terry fabric that is sourced through Tailored Projects. One of the most notable advantages of BEU is its established marketing strategies, particularly the launch of its website, which is functional and well-designed given its capacity to ease and improve the process of communication between the brand and its customers. As a sole proprietor business, their starting capital of Php 73,140 was acquired through the financial contribution of BEU’s shareholders. The expenses and transactions made after the launching of the business for resources, manufacturing costs, and packaging expenses are managed thoroughly; including the projected and actual sales monitored monthly for a better understanding of the business’ operation and sales performance. With BEU’s drive to prove and satisfy its customers with a quality product, improve and address common societal concerns as a social enterprise, advocate an idea of embracing one’s truest self, and establish a promising vision of becoming an ethical brand affiliated with outstanding plans, the business could highly provide a positive impact to the society from a global perspective.